(untitled) (LEARNing Landscapes, 2017)
This collaborative autoethnography explores how a doctoral peer writing group (PWG) has become an important means of fostering well-being among the authors, who are four doctoral scholars. Focusing on how writing in doctoral education can act as a barrier to well-being, defined as feeling part of a community, feeling balanced, and feeling motivated by forward momentum, each author shares her particular experiences with writing and how the PWG has contributed to her well-being. Based on the authors’ narratives, the article also suggests how PWGs may be useful in promoting well-being across several levels of education.